1989
DOI: 10.1083/jcb.108.3.1067
|View full text |Cite
|
Sign up to set email alerts
|

Growth and partial differentiation of presumptive human cardiac myoblasts in culture.

Abstract: Abstract. A cell culture model for human cardiac myogenesis is introduced. Human fetal myocardial cells were dissociated enzymatically, and cultured in a mitogen-rich medium that promoted the growth of presumptive cardiac myoblasts. Strains of human cardiac myoblasts were generated from different anatomical regions of the fetal heart. The cells could be cultured for at least 30 generations, or frozen and recovered for later use. Differentiation was induced by culturing the cardiac myoblasts in a mitogen-poor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…At present, GATA-6 has been linked to cardioblast proliferation whereas GATA-4 has been associated with terminal differentiation (12,15). In this respect, it is noteworthy that markers of later stages of cardiomyocyte differentiation-␣-and ␤-MHC genes-appear to be preferential GATA-4 targets whereas genes expressed in precardiomyocytes prior to the beating stage, such the natriuretic peptide (ANF and BNP) and PDGFR genes (16,24), are targeted by both GATA-4 and GATA-6. Since the adenovirus-mediated antisense strategy revealed that GATA-4 and GATA-6 are required for maintenance of the differentiated phenotype in postnatal cardiomyocytes, it could now be used to determine the role of these factors in embryonic myocytes.…”
Section: Discussionmentioning
confidence: 96%
“…At present, GATA-6 has been linked to cardioblast proliferation whereas GATA-4 has been associated with terminal differentiation (12,15). In this respect, it is noteworthy that markers of later stages of cardiomyocyte differentiation-␣-and ␤-MHC genes-appear to be preferential GATA-4 targets whereas genes expressed in precardiomyocytes prior to the beating stage, such the natriuretic peptide (ANF and BNP) and PDGFR genes (16,24), are targeted by both GATA-4 and GATA-6. Since the adenovirus-mediated antisense strategy revealed that GATA-4 and GATA-6 are required for maintenance of the differentiated phenotype in postnatal cardiomyocytes, it could now be used to determine the role of these factors in embryonic myocytes.…”
Section: Discussionmentioning
confidence: 96%
“…Cytokinesis can also occur in embryonic, neonatal, and some adult heart muscle cells under appropriate conditions [Chacko, 1973;Goode, 1975;Kohtz et al, 1989;Kaneko et al, 1984;Oberpriller et al, 1988;Tate and Oberpriller, 19891. Contractions cease in the area of the cleavage furrow [Kaneko et al, 19841, and myofibrils are disassembled [Goode, 19751. When cytokinesis is completed, daughter cells reassemble myofibrils and resume rhythmic contractions [Kaneko et al, 1984;Chacko, 19731.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the ANP gene has been used as a marker for the differentiation of atrial and ventricular myocytes, both in the developing heart in situ and in culture (Gilloteaux 1989;Kohtz et al 1989). As in the human heart in situ (Hamid et al 1987;Wharton et al 1988a, b;Yamada et al 1988), cultured fetal atrial and ventricular myocytes were ANP-like immunoreactive.…”
Section: Discussionmentioning
confidence: 97%
“…The mixed cell culture preparations described here may be a useful model for the direct study of the factors that influence ANP expression in human myocytes. It has already been reported that neuroblastoma cells in co-culture may increase the stability of ANP mRNA in human fetal ventricular myocytes (Kohtz et al 1989), and the presence of intracardiac neurones in the cultures from human fetal atria described would maintain any effect of the intrinsic neurones that innervate the heart in situ on ANP.…”
Section: Discussionmentioning
confidence: 98%